Regulator of G-protein signaling 5 (RGS5) protein: a novel marker of cancer vasculature elicited and sustained by the tumor’s proangiogenic microenvironment - Silini, Antonietta (SP Birkhäuser Verlag Basel, 2011)
We previously identified regulator of G-protein signaling 5 (RGS5) among several genes expressed by tumor-derived endothelial cells (EC). In this study, we provide the first in vivo/ex vivo evidence of RGS5 protein in the vasculature of ovarian carcinoma clinical specimens and its absence in human ovaries. Consistent with this, we show higher amounts of Rgs5 transcript in EC isolated from human cancers (as opposed to normal tissues) and demonstrate that expression is sustained by a milieu of factors typical of the proangiogenic tumor environment, including vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (FGF-2). Supporting these findings, we show elevated levels of Rgs5 mRNA in the stroma from strongly (as opposed to weakly) angiogenic ovarian carcinoma xenografts and accordingly, we also show more of the protein associated to the abnormal vasculature. RGS5 protein predominantly colocalizes with the endothelium expressing platelet/endothelial cell adhesion molecule-1 (PECAM-1/CD31) and to a much lesser extent with perivascular/mural cells expressing platelet-derived growth factor receptor-beta (PDGFR-β) or alpha smooth muscle actin (αSMA). To toughen the relevance of the findings, we demonstrate RGS5 in the blood vessels of other cancer models endowed with a proangiogenic environment, such as human melanoma and renal carcinoma xenografts; to the contrary, it was undetectable in the vasculature of normal mouse tissues. RGS5 expression by the cancer vasculature triggered and retained by the proangiogenic microenvironment supports its exploitation as a novel biomarker and opens the path to explore new possibilities of therapeutic intervention aimed at targeting tumor blood vessels.